RECIPROCAL CHARACTER VALUE IN THE BOOK OF TA'LIM MUTA'ALIM WITH CHARACTER EDUCATION IN INDONESIA AND GLOBAL ETHICS - Sri Haryanto; Robingun Suyud El Syam (Jurnal Scientia, 2022)
Formalistic education tends to emphasize academic achievement alone, weakening student character, so it is necessary to have integrative education that balances the cognitive, affective and psychomotor domains. With a research literature approach, it results that the concept of education in the book of muta'allim ta'lim is an integrative character education, covering three aspects of cognitive, affective and psychomotor. There are 11 character values in the book of ta'lim muta'allim that are relevant to character education in Indonesia, namely: religious character, fond of reading, peace-loving, independent, cooperation, tolerance, communicative, social care, environmental care, hard work, and appreciate achievement. The character values in the book of Ta'lim Muta'allim are also relevant to global ethics. It's just that global ethics is a product of humans so that in practice it often differs from one region to another, while character education in the book of ta'lim muta'allim, is based on values originating from religious teachings so that it is consistent in practice. Thus the values of character education in the ta'lim muta'allim book are relevant to character education in Indonesia and global ethics